Contribution of Santri in Supporting Food Security: Food Independent and Tirakat Ngrowot Islamic Boarding School Pathways (Journal Intellectual Sufism Research (JISR), 2024)
Food security is a situation where all people can have access to sufficient, safe and nutritious food to meet their food needs to lead an active and healthy life. Indonesia has weaknesses in terms of food security. The government through BAPANAS has several strategies to improve food security. On the other hand, Islamic boarding schools have consumption patterns that can help improve food security. This research aims to analyze the food security of Indonesia and examine the contribution of santri to food security. This research method uses library research. The results of this research are that santri have an important role in food security through diversifying food consumption through abstinence. This research can be used by the government to provide solutions to food problems in Indonesia.